Analisis Regresi Linier Berganda Dalam Estimasi Faktor-Faktor yang Mempengaruhi IPM di Sulawesi Selatan - Sianturi, Tiurmaida; Anggraini, Sepi; Deswan, Meisyy Laisa Usrini (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Human Development Index (HDI) is one of the indicators in assessing the development progress of a region that reflects the quality of life of the community based on the dimensions of health, education, and decent living standards. This study aims to analyze the effect of PDRB, IPG , and Average Years of Schooling (RLS) on HDI in South Sulawesi Province. This study uses multiple linear regression analysis methods on secondary data from BPS South Sulawesi for the period 2020-2023 which includes 24 districts / cities in South Sulawesi. The results showed that PDRB, IPG, and RLS had a positive and significant effect on HDI both partially and simultaneously. The model is able to explain 89% of the variation in HDI and fulfills all classical regression assumptions. The conclusion of this study emphasizes the importance of regional development policies that focus on improving the quality of education, sustainable economic growth, and gender equality to accelerate the achievement of human development in South Sulawesi.